Polysaccharide from aerial part of Chuanminshen violaceum alleviates oxidative stress and inflammatory response in aging mice through modulating intestinal microbiota - Zou, Yuan-Feng; JiZe, Xiao-Ping; Li, Cen-Yu; Zhang, Chao-Wen; Fu, Yu-Ping; Yin, Zhong-Qiong; Li, Yang-Ping; Song, Xu; Li, Li-Xia; Zhao, Xing-Hong; Feng, Bin; Huang, Chao; et al. (Frontiers in Immunology, 2023)
Aging is a biological process of progressive deterioration of physiological functions, which poses a serious threat to individual health and a heavy burden on public health systems. As population aging continues, research into anti-aging drugs that prolong life and improve health is of particular importance. In this study, the polysaccharide from stems and leaves of Chuanminshen violaceum was obtained with water extraction and alcohol precipitation, and then separated and purified with DEAE anion exchange chromatography and gel filtration to obtain CVP-AP-I. We gavaged natural aging mice with CVP-AP-I and performed serum biochemical analysis, histological staining, quantitative real-time PCR (qRT-PCR) and ELISA kit assays to analyze inflammation and oxidative stress-related gene and protein expression in tissues, and 16SrRNA to analyze intestinal flora. We found that CVP-AP-I significantly improved oxidative stress and inflammatory responses of the intestine and liver, restored the intestinal immune barrier, and balanced the dysbiosis of intestinal flora. In addition, we revealed the potential mechanism behind CVP-AP-I to improve intestinal and liver function by regulating intestinal flora balance and repairing the intestinal immune barrier to regulate the intestinal-liver axis. Our results indicated that C. violaceum polysaccharides possessed favorable antioxidant, anti-inflammatory and potentially anti-aging effects in vivo.